Guía para Operadores Profesionales de Herbicidas para el Control del Árbol de Corteza de Papel (Melaleuca) - Kenneth A. Langeland; Michael Meisenburg (EDIS)
SS-AGR-258-S, a 5-page illustrated fact sheet by K.A. Langeland and Michael Meisenburg, is the Spanish language version of 'Professional Applicator's Guide to Herbicides for Melaleuca Control.' It provides professionals with information on using herbicides as part of an integrated management program for invasive melaleuca trees. It describes available herbicides and application methods and when each should be used. Published by the UF Department of Agronomy, November 2006.